The Role of the State Administrative Court in Jurisdictional Disputes: A Case Study of Fadel Muhammad’s Lawsuit Against the DPD RI - Paselle, Enos; Maharani, Adji Puteri Mila; Norsabila, Annisa (Magister Ilmu Hukum, Universitas Krisnadwipayana, 2024)
This study provides an in-depth understanding of the jurisdictional dispute involving Fadel Muhammad and the DPD RI regarding the decision of the State Administrative Court (PTUN) of Jakarta. The results show that PTUN plays a crucial role in ensuring government accountability and protecting individual rights, but the decision in this case also highlighted tensions between the executive, legislative, and judicial powers. While PTUN has the authority to adjudicate administrative disputes, decisions related to political matters, such as the dismissal of Fadel Muhammad, present complexities that need to be carefully managed to avoid destabilizing the constitutional order. One of the main challenges is the enforcement of PTUN’s decisions, which remains susceptible to non-compliance by the government, potentially leading to legal uncertainty and undermining the effectiveness of the legal system in Indonesia. Therefore, further reforms are needed to strengthen the administrative law system and the judiciary to ensure that PTUN decisions are implemented effectively and fairly, thus maintaining the stability of democracy and the constitutional order in Indonesia.